Communication Model in Preventing Violence at Cibinong State High School 1 Bogor District - Syatir, Syatir (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Violence in schools has increased in recent years, and cases of this violence often have serious impacts, both on the victims and on the entire school community. Based on data from the Online Information System for the Protection of Women and Children, it shows that violence against children in 2019 was 12,285 children. This figure has increased in 2020 to 12,425 children. Not stopping at these numbers, in 2022 the amount of violence against children will increase sharply to 15,972 children. Violence can take the form of rape, beatings, confinement, neglect, kidnapping, murder and there is also violence that makes children anxious. Therefore, this research examines the communication model for preventing violence at State Senior High School 1 Cibinong, Bogor Regency. The research design used is descriptive qualitative with data analysis consisting of data reduction, data presentation, and drawing conclusions and verification. The research results show that implementing an appropriate communication model, which allows messages from teachers to students to be received and understood, can help change student behavior to avoid violence.